THE CHALLENGE OF INSECURITY ON FOOD SECURITY IN DUTSIN-MA LOCAL GOVERNMENT AREA, NIGERIA: SIGNAL OF AN IMPEDING CRISIS - AHMED , ALIYU TANKO; GYONG , YERIMA EMMANUEL; ISYAKU, AUWAL (JOURNAL OF ECONOMICS AND ALLIED RESEARCH, 2024)
This paper investigated the challenge of insecurity on food security in Dutsin-Ma local government area, Katsina State. The method of data collection was the use of Survey. Questionnaires was administered for a sample of 240 respondents across the four wards in the study area, which include Dutsin-Ma A, Dutsin-Ma B, Shema and Dabawa The analytical technique used was descriptive statistics and chi-square test, using IBM SPSS Statistics 20. The theoretical framework is the human security theory. The findings revealed that 99.1% of insecurity challenge made up of kidnapping. Also killing and attack on farm crops constitute 91.1% and 79.1% of insecurity respectively. The findings established that 99.1% of the respondents indicated there is shortage of food in the study area. The result shows that majority (76.8%) opined that insecurity led to high price of food items in the study area, 74.4% opined that insecurity reduced food crop production in the study area. Hence leading to food shortage in the study area and so faced the challenge of accessing sufficient and nutritious food in the study area. The test of hypothesis revealed that that insecurity has negative effects on food security in Dutsin-Ma local government area of Katsina State Nigeria. Based on the findings, There is need for synergy between the community, security agents, and the Katsina State Government to improve the security architecture. This can be done by engaging the people in the local communities in both the urban and rural settlements. Therefore the community leaders should be engaged and a policy system for reward should be introduced at every level in the community.